Identity Politics Approaching the 2024 Election through Social Media Through Sociology of Religion Perspective - Abdul Majid; Said Amirulkamar (Universitas Muhammadiyah Yogyakarta, 2023)
Towards the democratic party in Indonesia, identity politics has become a tool used for political campaigns to influence voters. The focus and purpose of this study are to analyze the dynamics of identity politics approaching the 2024 elections through social media from the sociology of religion perspective. This study used the theory of identity politics put forward by Manuel Castells (2007). The method used was a descriptive qualitative approach. Data sources were obtained through websites, journals and social media. Data analysis techniques used content analysis techniques and Nvivo 12 plus analysis techniques. The results showed a review of Manuel Castells’ theory (2007) regarding legitimacy, resistance, and project identity. Political parties are building good track records and campaigning on platforms that can meet voters' expectations, the concept of